Occurrence of antibiotics and antibiotic resistance genes at various stages of different aquaculture modes surrounding Tai Lake, China - Wu, Congcong; Ye, Haitao; Xu, Mingzhu; Zhao, Xuan; Zhao, Xuejie; Li, Lina; Li, Mingzhi; Wei, Yanfei; Li, Yuru; Hu, Baolan (Frontiers in Microbiology, 2025)
IntroductionAquaculture is an important source of antibiotics and ARGs in environmental waters. However, the occurrence of antibiotics and ARGs under different modes and stages of aquaculture has rarely been systematically studied.MethodsThis paper uses qPCR, LC-MS, and High-Throughput sequencing across different culture modes and stages to investigate antibiotics, resistance genes, and microbial communities in the water bodies, and analyze contamination differences between these modes.ResultsThe quinolone and chloramphenicol were the main antibiotics, and the highest absolute abundance genes were quinolone resistance genes (qnrB) and quinolone resistance genes (sul1), with the mobile genetic element (MGE) intI1, both of which exhibited a gradual seasonal increase. Microbial diversity also varies seasonally, especially with a gradual increase in the abundance of some pathogenic bacteria (Flavobacterium). Antibiotics and resistance genes were found at higher levels in fish ponds compared to shrimp and crab ponds, while they were lower in shrimp and crab ponds that utilized the ecological mode ponds than in the traditional culture mode ponds.ConclusionOur study presents a comprehensive characterization of antibiotics and ARGs in aquaculture waters from various perspectives. Ecological aquaculture modes contribute to reducing antibiotic and resistance gene pollution in water bodies. These findings will support the optimization of aquaculture mode and antibiotic usage to the green and sustainable development of aquaculture finally.